Samuel Wylie Crawford papers - Crawford, Samuel Wylie, 1827-1892.
Correspondence, memoranda, diary, registers and returns of troops and artillery, sketches, photographs, and other papers relating chiefly to events while Crawford was an assistant surgeon at Fort Sumter during the early months of 1861. Includes correspondence of F.W. Pickens with Jefferson Davis, copies of correspondence between Robert Anderson and G.T. Beauregard before the bombardment of Fort Sumter, and a statement by David Dixon Porter concerning the side-wheel steamer Powhatan and the provisioning of Fort Sumter. Correspondents include Ellison Capers, Maxcy Gregg, Robert E. Lee, A.G. Magrath, C.G. Memminger, John C. Pemberton, and R.S. Ripley.
Physician and army officer of Pennsylvania.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Robert, -- 1805-1871 -- Correspondence; Beauregard, G. T. -- 1818-1893 -- Correspondence; Capers, Ellison, -- 1837-1908 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Gregg, Maxcy, -- 1814-1862 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Magrath, A. G. -- 1813-1893 -- Correspondence; Memminger, C. G. -- 1803-1888 -- Correspondence; Pemberton, John C. -- 1814-1881 -- Correspondence; Pickens, F. W. -- 1805-1869 -- Correspondence; Porter, David D. -- 1813-1891.; Ripley, R. S. -- 1823-1887 -- Correspondence; United States. -- Army -- Supplies and stores; Powhatan (Side-wheel steamer); Military supplies; Fort Sumter (Charleston, S.C.) -- Siege, 1861.; Charleston (S.C.) -- History -- Civil War, 1861-1865.; South Carolina -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Medical care; Army officers; Physicians